Urinary protein markers of renal dysfunction in full-term newborns with disorders of early neonatal period - Juliya Hodovanets; Anastasiya Babintseva; Nicholas Tibor Longford; Ludmila Agafonova (Hygeia Press di Corridori Marinella, 2018)
Background: Urinary proteins may help to understand the physiology and diagnose renal dysfunction in sick infants. The renal function in ill full-term newborns with disorders of early neonatal period by means of detecting specific protein biomarkers in the urine was studied. Materials and methods: A prospective cohort study on 205 full-term newborns was performed including 55 healthy infants, 55 newborns with clinical signs of moderate disorders of early neonatal period, 50 newborns with severe neonatal disorders without acute kidney injury (AKI), and 45 newborns with both severe neonatal disorders and AKI. The urinary concentrations of total protein (UTPr), albumin (UAlb), immunoglobulin G (UIgG), α1-microglobulin (Uα1-MG), and β2-microglobulin (Uβ2-MG) were determined by means of laboratory tests. Results: As compared to healthy newborns, full-term neonates with moderate disorders of early neonatal period developed dysfunction of the glomerular membrane (selective proteinuria with excessive excretion of UAlb), and proximal tubules (increased Uα1-MG). More severe neonatal disorders in term newborns are accompanied by selective proteinuria together with more pronounced tubular failure (excessive urinary excretion of Uα1-MG and Uβ2-MG). Formation of AKI in term infants is associated with complex disorders of all structural elements of the nephron, manifested by extremely high levels of total protein markers of glomerular (UTPr, UAlb and UIgG) and tubular (Uα1-MG and Uβ2-MG) dysfunction in urine. Conclusions: The measurement of urinary protein biomarkers in sick full-term newborns with clinical signs of disorders of early neonatal period demonstrated renal dysfunction not only in infants with AKI. The biochemical changes found in critically ill newborns require timely diagnosis promoting the right choice of intensive therapy with the aim to prevent the development of severe renal pathology and chronic renal failure in the future.